Sarcopenia as a prognostic indicator in colorectal cancer: an updated meta-analysis - He, Jie; Luo, Wei; Huang, Yuanyuan; Song, Lingmeng; Mei, Yang (Frontiers in Oncology, 2023)
Background Sarcopenia, often observed in the elderly, is associated with declining skeletal muscle mass and impaired muscle function. This condition has been consistently linked to a less favorable prognosis in various malignancies. Computed tomography (CT) is a frequently employed modality for evaluating skeletal muscle mass, enabling the measurement of the skeletal muscle index (SMI) at the third lumbar vertebra (L3) level. This measurement serves as a defining criterion for sarcopenia. The meta-analysis dealt with evaluating the promise sarcopenia held as a prognostic indicator in individuals with colorectal cancer. Methods Research relevant to the subject was determined by systematically searching PubMed, Embase, Web of Science, WANFANG, and CNKI (up to June 11, 2023, published studies). In this meta-analysis, the incidence of sarcopenia in individuals with colorectal cancer was combined to analyze the disease-free survival (DFS), overall survival (OS), and cancer-specific survival (CSS) of these individuals with and without sarcopenia. The included research was evaluated for quality per the Newcastle-Ottawa Scale (NOS) score. In the multivariate analysis of each study, the direct extraction of hazard ratio (HR) with a 95% confidence interval (CI) was executed. STATA 11.0 was applied to integrate and statistically analyze the data. Results Overall 20 articles participated in this meta-analysis. A 34% incidence of sarcopenia was noted in colorectal cancer. The presence of sarcopenia denoted a decrease in OS (HR=1.72,95% CI=1.45-2.03), DFS (HR=1.42,95% CI=1.26-1.60) and CSS (HR=1.48,95% CI=1.26-1.75) in individuals with colorectal cancer. In addition, the subgroup analysis depicted a pattern consistent with the overall analysis results. Conclusion CT-defined sarcopenia exhibits promise as an indicator of survival prognosis in individuals with colorectal cancer. Future studies need a more rigorous definition of sarcopenia to further verify these findings. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023431435.